Prevalence and antifungal susceptibility of Candida species among pregnant women attending a school maternity at Natal, Brazil. (12th July 2018) - Brandão, L.D.S.; Boniek, D.; Resende Stoianoff, M.A.; da Mata, F.M.R.; de Azevedo, P.R.M.; Fernandes, J.V.; Andrade, V.S.
Abstract : Abstract: Vulvovaginal candidiasis (VVC) is an inflammatory disease of the vulva and vagina caused by different yeasts of the genus Candida which is responsible for infection in pregnant patients who attended Maternidade Escola Januário Cicco, Rio Grande do Norte, Brazil. From 41 samples, 19 yeasts were identified phenotypically as Candida albicans and one as Candida glabrata which is reported as the non‐ albicans species most frequently isolated from vulvovaginitis. The susceptibility to selected antifungal agents (flucytosine, fluconazole, voriconazole, amphotericin B, caspofungin and micafungin) was determined, and the association between patient‐related signs and symptoms aided the construction of an epidemiological profile. Antifungal susceptibility testing performed by automated method showed that all strains were sensitive to the drugs tested, including the C. glabrata specimen despite its known resistance or dose‐dependent susceptibility to azole derivatives. Regarding patient signs and symptoms, no statistically significant association between these and the establishment of VVC was found. It can be concluded that the laboratorial diagnosis of VVC is necessary prior to the administration of treatment, since only 48·78% of the patients had VVC but for all of them antifungal therapy were prescribed. Significance and Impact of the Study: Vulvovaginal candidiasis (VVC) is a problem that affects a significant number of pregnant women worldwide. This type of fungal infection generates great discomfort due to the symptomatology and difficulties of diagnosis and treatment. In view of the scarcity of data in the State of Rio Grande do Norte, Brazil, regarding studies carried out on fungal populations of the genus Candida associated with VVC in pregnant women, this study considered relevant, the phenotypic and genotypic identification of the species, to estimate the prevalence, to determine their susceptibility to the antifungal and to correlate with signs and symptoms. Significance and Impact of the Study: Vulvovaginal candidiasis (VVC) is a problem that affects a significant number of pregnant women worldwide. This type of fungal infection generates great discomfort due to the symptomatology and difficulties of diagnosis and treatment. In view of the scarcity of data in the State of Rio Grande do Norte, Brazil, regarding studies carried out on fungal populations of the genus Candida associated with VVC in pregnant women, this study considered relevant, the phenotypic and genotypic identification of the species, to estimate the prevalence, to determine their susceptibility to the antifungal and to correlate with signs and symptoms.